Thoracotomy in Thoracic Injuries: Results from a Tertiary Referral Hospital - Ozyurtkan, Mehmet Oguzhan; Balci, Akin Eraslan; Cakmak, Muharrem (Springer Heidelberg, 2010)
Introduction: Critically injured patients may require thoracotomy after a thoracic injury. This study is a retrospective analysis of the results of thoracotomy in patients with thoracic injury. Materials and Methods: Injured patients with detectable signs of life on arrival at the hospital and who underwent thoracotomy within 4 h of the injury were investigated. Demographic data and medical records were reviewed for associated injuries, indications, intraoperative findings, and outcomes. The factors affecting the mortality were analyzed. Results: Between April 2003 and January 2009, 488 patients with thoracic injury (blunt/penetrating = 73.7%/26.3%) were treated, and 20 (4.1%) underwent thoracotomy (male/female = 17/3, mean age = 27 +/- 9 years). The injury was penetrating in 15 (11.7%) and blunt in five (1.4%). None of them required an endotracheal intubation at the scene or in transit. The mean transport time was 58 min. Severe and continuous hemothorax (80%), massive air leak, major vessel injury, and trauma causing an open chest wall defect with bleeding were indications of the thoracotomy. Eighty-five percent survived after the surgery (penetrating/blunt = 86.6%/80%). The mean injury severity score (ISS) of the survivors was lower (21 9 vs. 39 +/- 10, p = 0.05). Mortality was associated with a lower Glasgow coma scale (GCS) (p = 0.03), a higher ISS (p = 0.05), and a longer transport time (p = 0.05). Conclusions: Thoracotomy after thoracic injury is a life-saving procedure in selected cases. Lower GCS and higher ISS are associated with increased mortality. Early transport and quick attempts to diagnose the indications necessitating thoracotomy play a significant role in improving the outcome.
Keywords: Chest trauma; Emergency surgery; Thoracic; Thoracic trauma